Patient Satisfaction With Meal Service With Leftovers At Grandmed Hospital Lubuk Pakam - ginting, wira maria; Widyaningsih, Fadlilah; Hayanti Panjaitan, Delita (JURNAL KESMAS DAN GIZI (JKG), 2024)
Food service is an important issue in the hospital environment, and patient satisfaction levels are often indicated by food consumption and waste. The current study compared patient satisfaction in hospital areas and other factors and determined the relationship between patient satisfaction and food waste. This quantitative study was conducted in RS. GrendMed Lubuk Pakam. Patients in these hospitals were asked to fill out a questionnaire consisting of three parts: general information, patient satisfaction questionnaire (Patient Satisfaction Questionnaire for Acute Care Hospital Food Service). A total of 74 patients participated. The results showed that overall, 18.9% (finished and satisfied), 39.2% (not finished and satisfied), and 41.9% (Not satisfied and not finished). Satisfaction with hospital food varies according to the service of each patient with health conditions. However, the results also showed that satisfaction with hospital food service was significantly associated with food waste (p value = 0.000). Various factors in hospital food service, especially food quality, should be improved to motivate patients to consume hospital food..